Tata Kelola Perusahaan Dan Pengungkapan Sukarela - Irza Shara Hervina; Riska Forma Madania; Herry Subagyo (STEKOM PRESS, 2022)
This study examines the correlation between corporate governance and voluntary disclosure of information. The sample used was companies that conducted an IPO on the Indonesia Stock Exchange in 2018. Using purposive sampling technique, 129 data were obtained. The analytical tool used was multiple regression analysis with SPSS version 25. The study found that the number of board of directors influenced voluntary disclosure of information, while foreign ownership, institutional ownership, management ownership, public share ownership, independent commissioners, and audit committees were not found to influence voluntary disclosure.GCG, . voluntary disclosure, foreign ownership, institutional ownership